2023
DOI: 10.1212/nxi.0000000000200109
|View full text |Cite
|
Sign up to set email alerts
|

Therapies in Stiff-Person Syndrome

Abstract: Among the glutamic acid decarboxylase (GAD)-antibody–spectrum disorders, the most common phenotypic subset is the stiff-person syndrome (SPS), caused by impaired GABAergic inhibitory neurotransmission and autoimmunity characterized by very high titers of GAD antibodies and increased GAD-IgG intrathecal synthesis. If not properly treated or untreated because of delayed diagnosis, SPS progresses leading to disability; it is therefore fundamental to apply the best therapeutic schemes from the outset. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…12 Rather, the limiting factor in the use of IVIg as continuing therapy in LOSPS is more related to tolerance and the existence of serious comorbidities due to cardiac problems, history of thromboembolic events, or poor venous access that necessitate early discontinuation; further subcutaneous IgG, which is preferable when IVIg is not tolerated or not considered safe, cannot be given to those LOSPS receiving anticoagulant therapies. Accordingly, in certain circumstances, rituximab which is also effective in 40% of SPS patients based on our large controlled study, 14 may be considered earlier in the immunotherapeutic algorithm in LOSPS, compared to their younger counterparts, to prevent disability. Toward this goal, the newly discussed future immunotherapies in SPS, 14 if proven effective, may be also considered earlier in LOSPS when rituximab is not effective.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…12 Rather, the limiting factor in the use of IVIg as continuing therapy in LOSPS is more related to tolerance and the existence of serious comorbidities due to cardiac problems, history of thromboembolic events, or poor venous access that necessitate early discontinuation; further subcutaneous IgG, which is preferable when IVIg is not tolerated or not considered safe, cannot be given to those LOSPS receiving anticoagulant therapies. Accordingly, in certain circumstances, rituximab which is also effective in 40% of SPS patients based on our large controlled study, 14 may be considered earlier in the immunotherapeutic algorithm in LOSPS, compared to their younger counterparts, to prevent disability. Toward this goal, the newly discussed future immunotherapies in SPS, 14 if proven effective, may be also considered earlier in LOSPS when rituximab is not effective.…”
Section: Discussionmentioning
confidence: 90%
“…The experience from the present series suggests that personalized treatment regimens are required for older patients with SPS because their poor tolerance to antispasmodics and sedating analgesics necessitates the need for earlier initiation of immunotherapy with IVIG, which is considered first-line immunotherapy. 14 Because SPS is a progressive disease, 10 treatment with IVIg should start as soon as antispasmodics are ineffective or poorly tolerated. 14 Despite their rapidly evolving disability however, our data show that LOSPS patients did not seem to have a significantly lower rate of response to IVIg because all nine patients were treated with IVIg and only two were non-responders; this represents a response rate similar to our prior study which identified a 67% responder rate to IVIg, although in LOSPS their response was partial and seemed to decline faster.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations